Rewriting logic and its applications : 11th International Workshop, WRLA 2016, held as a satellite event of ETAPS, Eindhoven, the Netherlands, April 2-3, 2016, Revised selected papers - WRLA (Conference) 2016 : Eindhoven, Netherlands); Lucanu, Dorel; ETAPS (Conference) 2016 : Eindhoven, Netherlands) (Switzerland : Springer, 2016)
This book constitutes the thoroughly refereed post-workshop proceedings of the 11th International Workshop on Rewriting Logic and its Applications, WRLA 2016, held as a satellite event of ETAPS 2016, in Eindhoven, The Netherlands, in April 2016. The 8 revised full papers presented together with 2 invited papers and 3 abstracts were carefully reviewed and selected from 14 submissions. The papers cover several topics such as: foundations; rewriting as a logical and semantic framework; rewriting languages; verification techniques; and applications.
Foundations -- Rewriting as a logical and semantic framework.-Rewriting languages -- Verification techniques -- Applications.
Includes bibliographical references and author index.
Online resource; title from PDF title page (SpringerLink, viewed August 25, 2016).
Keywords: Computer logic -- Congresses; Logique informatique -- Congrès.; Software Engineering; Computer programming -- software development; Programming & scripting languages: general; Mathematical theory of computation; Computer science; Computers -- Software Development & Engineering -- General; Computers -- Programming -- General; Computers -- Programming Languages -- General; Mathematics -- Logic; Computers -- Online Services -- General; Informatique; Computer logic; Conference papers and proceedings